Corporate Governance, Performance, and Financial Statements Publication as Moderation on Company Value in Indonesia - Suwardi Bambang Hermanto; Ikhsan Budi Riharjo (Journal of World Conference (JWC), 2020)
The research objective was to analyze the influence of corporate governance and performance, as well as the publication of financial statements as the moderation of company value. Institutional ownership variables, number of commissioners, number of directors, and number of audit committees and independent commissioners as corporate governance. Return on asset variables as performance, and audit delay as the publication of financial statements, and Tobin's Q as a company value. The research objects were 70 public companies on the Indonesia Stock Exchange, with a sample of 122 observations of financial statements from 2013-2017. The results showed that the number of commissioners, audit committees and return on assets had a positive effect on firm value. Publication of financial statements affects the value of the company, and moderates the effect of financial performance on firm value. Whereas institutional ownership, the number of directors and independent commissioners does not affect